A comparative study of standing fleshed foot and walking and jumping bare footprint measurements. Issue 5 (September 2018) - Howsam, Nicolas; Bridgen, Andrew
Abstract: Approximating true fleshed foot length and forefoot width from crime scene footprints is primarily based on anecdotal observations and fails to consider effects of different dynamic activities on footprint morphology. A literature search revealed numerous variables influencing footprint formation including whether the print was formed statically or dynamically. The aim of this study was to investigate if length and width measurements of the fleshed foot differ to the same measurements collected from walking and jumping footprints. Measurements of standing right foot length and forefoot width were collected from thirteen participants. Walking and jumping right footprints were then obtained using an Inkless Shoeprint Kit and digitally measured with GNU Image Manipulation Programme. Descriptive analysis compared standing fleshed foot length and forefoot width against the same measurements taken from walking and jumping footprints with and without ghosting. Results suggested walking footprint length with ghosting ( x ¯ = 268.61 mm) was greater than standing fleshed foot length ( x ¯ = 264.3 mm) and jumping footprint length with ghosting ( x ¯ = 261.57 mm). However, standing fleshed foot length was found to be greater than walking ( x ¯ = 254.85 mm) or jumping ( x ¯ = 255.63 mm) footprint lengths without ghosting. Forefoot widths showed standing fleshed foot width ( x ¯ = 105.66 mm) was greater than walking ( x ¯ = 95.63 mm) or jumping ( x ¯ = 98.03 mm) footprint widths. This study identifies variation in measurements of the standing fleshed foot and those of walking and jumping footprints, including variability between different dynamic states. Highlights: Walking footprint length with ghosting was greater than static fleshed foot length. Dynamic footprint length with ghosting was greater in walking than jumping. Static foot length was greater than dynamic footprint lengths without ghosting. Dynamic footprint length without ghosting was greater in jumping than walking. Standing forefoot width was greater than jumping or walking footprint widths.